SAT0273 The Characteristics and Predictors of Minimal Disease Activity in Patients with Psoriatic Arthritis on TNF Blockers. (23rd January 2014) - Haddad, A.; Thavaneswaran, A.; Ruiz Arruza, I.; Chandran, V.; Cook, R.; Gladman, D.
Abstract : Background: The introduction of TNF blockers in psoriatic arthritis (PsA) has altered the disease course and was shown to reduce disease activity and radiographic progression. Clinical remission requires achieving disease quiescence in all disease domains. A state of Minimal Disease Activity (MDA) was defined and validated as a target for treatment in PsA. However, data regarding the characteristics and prognostic outcomes of patients in MDA state in observational cohorts while being on TNF blockers is scarce. Objectives: To identify disease characteristics of patients with PsA who achieve MDA while on TNF blockers and to identify predictors for MDA. Methods: Patients were recruited from a single centre cohort. All patients fulfilled the CASPAR criteria and were followed regularly at 3-6 months intervals. TNFα blockers were prescribed when patients failed to standard of care. Patients were considered in MDA when met a least 5/7 of the following criteria: Tender joint count≤1; swollen joint count ≤1; psoriasis activity and severity index ≤1 or body surface area ≤3; patient pain visual analog scale (VAS) score of ≤15; patient global disease activity VAS score of ≤20; Health Assessment Questionnaire (HAQ) score ≤0.5; and tender entheseal points ≤1. Patients achieving MDA were compared to patients who did not achieve MDA using descriptive statistical tests. A proportional odds discrete time survival analysis model was used to identify predictors of the first onset of MDA. Results: 306 patients in the database were treated with anti-TNF agents, Of whom 22 were in MDA at baseline and 57 were prescribed anti-TNF agents prior to enrolment. The remaining 227 were in non-MDA state and constituted the study population. 146/227 patients achieved MDA after an average of 1.30 (1.51) years and for a mean duration of 3.46 (2.25) years. Among patients who achieved MDA, at baseline they were more males (68.5% vs. 59.3%, P=0.01), younger at the age diagnosis (34.5 vs. 38.8, P=0.03), had a lower active joint count (8.7 vs. 15.3, P=0.0002), more likely to have clinical damage (74.4% vs. 48.6%, P=0.0003) and axial involvement (53.9% vs. 8.3%, P=0.001) compared to patients that didn't achieve MDA. Patients with non-MDA state had higher BMI (31.6 vs. 28.5, P=0.02) at baseline, were more classified with functional class III/IV (32.9% vs. 10.1, P<0.0001%) and had a lower SF-36 physical (29.1 vs. 43.9) and mental (42.6 vs. 49.8, P=0.006) component scores compared to the MDA group. The majority of patients in both groups were also treated with DMARDs and NSAIDs. No significant difference was found in disease duration, alcohol, smoking, ESR, CRP, PASI score or radiographic damage between the two groups. The survival analysis showed that after adjusting for characteristics at each visit such as sex, age, duration of disease, abnormal ESR, PASI, obesity and active joint count that only active joint count (OR=0.70 CI 0.57-0.88, P=0.002) and PASI score (OR=0.84 CI 0.72-0.99, P=0.03) lowered the odds of achieving MDA. Conclusions: 63% of the study group achieved MDA after an average duration of 1.3 years. Only lower active joint count and PASI score were predictors of response to treatment with TNF blockers. Disclosure of Interest: None Declared